Relationship between black soybean polyphenols and seed coat color during boiling process - Mizuno, Naho; Noshima, Yuka; Toda, Toshiya (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2024)
This study investigated the change in color of black soybean seed coats during boiling process owing to the reaction between iron ions and polyphenols, especially non-extractable proanthocyanidins (NEPAs). Beans boiled three times in water were discolored to reddish brown, and the content of anthocyanins (cyanidin 3-glucoside) was less than 1 % of that of raw beans; however, they turned jet black when boiled in 5 mmol/L ferrous sulfate solution. Seed coats from which extractable polyphenols such as anthocyanins and low-molecular weight flavanols were completely removed by extraction with the aqueous–organic solvents had a reddish brown color; however, NEPAs remained in them. Therefore, it was considered that the main mechanism by which the black color of the seed coat is maintained using iron agents during boiling process is the reaction of iron ions with NEPAs and not anthocyanins.